Prospective evaluation of immediate reconstruction after mastectomy. - Eberlein, T J (1993)
OBJECTIVE: The authors prospectively studied the impact of immediate breast reconstruction on patients undergoing mastectomy. SUMMARY BACKGROUND DATA: Despite the advocation of a breast-conserving approach to the treatment of breast cancer, many women continue to medically require or choose mastectomy for the treatment of breast cancer. In recent years, immediate breast reconstruction has become an alternative to either mastectomy alone or to delayed reconstruction. METHODS: A prospective database of 216 patients who underwent mastectomy with immediate reconstruction was established. In this series, 94 procedures involved implants or tissue expanders, and 124 tissue transfers were performed. RESULTS: The overall complication rate was 15.3%; only 9% of patients who underwent autologous tissue transfers required secondary procedures. When implants were performed, the overall rate of prosthetic loss was 8%. The majority of patients (n = 101) underwent transverse rectus abdominis musculocutaneous (TRAM) flaps. Twenty-six of the 38 (17.5%) patients who required transfusion were from this group. Partial flap losses in this group (7%) were correlated to a history of heavy smoking. With a median follow-up of 33.2 months, only two patients had recurred locally. According to patient opinion, autologous tissue transfers resulted in a statistically better cosmetic result. CONCLUSIONS: Immediate reconstruction can be performed safely and with excellent cosmetic results.